Singlet Oxygen Quenching Activities Of Phenolic Extract From Lemon Grass Leaves (Cymbopogon citratus Stapf) - Suryanto, Edi; Katja, Dewa Gede; Wehantouw, Frenly (CHEMISTRY PROGRESS, 2019)
Lemon grass (Cymbopogon citratus Stapf) is a traditional food ingredient characterized by its specific andrefreshing aroma. This objectives of study was determined phytochemical contents and the effect of lemongrass leaves extract in photooxidation linoleic acid and ascorbic acid in system model. Lemon grass leaves wasextracted sequentially with hexane and methanol. The photooxidation reaction system was consisted of linoleicacid 0.03 M in ethanol containing 0.017 mM erythrosine as sensitizer the reaction mixture was exposed under4000 lux fluorescent light up to 5 hours while ascorbic acid 200 μg/mL in phospat buffer solution (pH 7.5)containing 0.0068 mM erythrosine as sensitizer illuminated for 20 minutes. Analyses of phytochemical based ontotal phenolic and flavonoid. Analyses of photooxidation of linoleic acid based on peroxide value anddegradation of ascorbic acid was analyzed using the spectrophotometer at λ 265 nm. The total phenolic andflavonoid content in hexane extract showed the highest phenolic content than methanol extract. Hexane extract1500 ppm exhibited singlet oxygen quenching effect on photooxidation linoleic acid compared with methanolextract, peroxide value 3.57 and 3.72 meq/kg after 5 hours illumination, respectively. Hexane extract 100 ppmalso exhibited singlet oxygen quenching effect on photooxidation ascorbic acid compared with methanol extract,ascorbic acid content 185.44 and 76.67 mg/kg after 5 hours illumination, respectively. It’s concluded thathexane extract of lemon grass leaves contain phenolic component that have singlet oxygen quencher activity.